TREM2 in MASH: integrating lipid metabolism and immune response - Shi, Shuyi; Zhou, Yangyang; Zhang, Haiming; Zhang, Junli (Frontiers in Immunology, 2025)
Metabolic dysfunction-Associated Steatohepatitis (MASH), a progressive liver disease characterized by disturbances of lipid metabolism and chronic inflammation response in liver has become the most prevalent chronic liver diseases worldwide. Recent single-cell transcriptomic studies in both humans and mice have identified a distinct population of liver macrophages characterized by the expression of Triggering Receptor Expressed on Myeloid Cells 2 (TREM2), also be known as lipid-associated macrophages (LAMs), is highly expressed in macrophages under metabolic stress conditions. Several studies have demonstrated that TREM2+ macrophages play a crucial role in lipid metabolism and immune responses, contributing to the reversal of MASH. This review provides a comprehensive overview of the current evidence on the roles of TREM2+macrophages in regulating lipid metabolism and immune responses in MASH, with emphasis on the functions of TREM2+ macrophages in lipid handling and inflammation regulation, which could provide novel insights into the pathogenesis of MASH and inform targeted therapeutic strategies.